Chest associated to motor physiotherapy acutely improves oxygen saturation, heart rate and respiratory rate in premature newborns with periventricular-intraventricular hemorrhage - de Abreu, Luiz Carlos; Valenti, Vitor E.; de Moura Filho, Oseas Florencio; Vanderlei, Luiz Carlos M. [UNESP]; de Carvalho, Tatiana Dias; Vertamatti, Maria A. F. [UNESP]; Oliveira, Adriana G.; Moreno, Isadora L.; Goncalves, Ana Clara C. R.; Siqueira, Arnaldo A. F. (Drunpp-sarajevo, 2011)
Background: The literature presents contradictory data regarding physiotherapy effects on premature newborns. Thus, we aimed to evaluate the effects of chest associated to motor physiotherapy on oxygen saturation (SO(2)%), heart rate (HR) and respiratory rate (RR) in premature newborns with peri-intraventricular hemorrhage (PIVH).Methods: This study was performed in an intensive care unit. We included newborns with birth weights below 2,000g and we used Papille classification, which classifies PVIH into four grades according to the degree. Newborns were divided in control (n=38) and PIVH (n=32) groups. The protocol followed this sequence: monitoring, physiotherapy, respiratory therapy, physiotherapy and motor monitoring. We compared the cardiorespiratory parameters between before the first physiotherapy session and after the third (last) physiotherapy session in one day.Results: SO(2)% increased after physiotherapy procedures in control and PIVH groups (p<0.05). Furthermore, HR and RR decreased after physiotherapy treatment in PIVH group (p<0.001).Conclusion: Chest associated to motor physiotherapy treatment acutely improved SO(2)%, HR and RR in premature PIVH newborns. Thus, we recommend performing chest associated to motor physiotherapy in neonatal critically ill newborns.
Keywords: Cerebral hemorrhage; Infant, Newborn; Physical Therapy (Specialty); Infant, Premature, Diseases